1999
DOI: 10.1017/s0334270000010602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of layered shells from a finite set of viscoelastic materials

Abstract: The method suggested earlier for solving the problems of optimal design from a limited set of elastic materials is generalized to a viscoelasticity case. The computational experiment for the problem of free oscillations of a spherical shell shows that characteristics of a viscoelastic layered structure may be improved due to peculiarities of wave propagation through the boundaries of layers made of different materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Solving problems of the optimal design of layered structures, Bondarev et al [1] showed that the damping level of a multilayer spherical shell made of a given set of viscoelastic materials can be increased by changing the relative position and relative thickness of the layers. Solving problems of the optimal design of layered structures, Bondarev et al [1] showed that the damping level of a multilayer spherical shell made of a given set of viscoelastic materials can be increased by changing the relative position and relative thickness of the layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Solving problems of the optimal design of layered structures, Bondarev et al [1] showed that the damping level of a multilayer spherical shell made of a given set of viscoelastic materials can be increased by changing the relative position and relative thickness of the layers. Solving problems of the optimal design of layered structures, Bondarev et al [1] showed that the damping level of a multilayer spherical shell made of a given set of viscoelastic materials can be increased by changing the relative position and relative thickness of the layers.…”
mentioning
confidence: 99%
“…We formulate the following problem (see [1]): from a given set of materials, it is required to construct a multilayer shell with limited weight that ensures a minimum value of the selected quality criterion:…”
mentioning
confidence: 99%